The impact of financial literacy, attitude, and behavior on financial well-being among Metro Manila residents - Bana Lim, Erika Shaine Chong (Animo Repository, 2021)
This study focused on the impact of financial literacy, attitude, and behavior on financial well-being among 226 Filipino respondents residing in Metro Manila. Theories such as behavioral finance, financial planning, life-span development, and financial psychology expounds on the direct, indirect, and mediating effect of financial attitude and financial behavior on the relationship between financial literacy and financial well-being. The following instruments were used: Financial Quantitative Literacy Assessment for Financial Literacy (Nye and Hillyard, 2013), The Financial Management Behavior Scale (FMBS) for Financial Behavior, Financial Management Attitude Scale for Financial Attitude, and CFPB (Consumer Financial Protection Bureau) Financial Well-Being Scale for Financial Well-Being. A confirmatory factor analysis was utilized to evaluate the validity of factor loadings. Also, Structural Equation Modeling (SEM) approach was performed to generate a path analysis relating the above-mentioned variables. The study showed that financial literacy, attitude, and behavior were significant predictors of financial well-being. It also showed that both financial attitude and behavior partially mediated the relationship between financial literacy and financial well-being. Keywords: Financial Literacy, Financial Attitude, Financial Behavior, Financial Well-Being, Structural Equation Modelling